A COMPARATIVE ANALYSIS OF RITES OF PASSAGE IN UZBEK FOLK CULTURE WITH A SPECIAL FOCUS ON KAHRAMANMARAŞ FOLK CULTURE (Eureka Journal of Language, Culture & Social Change, 2026)
This article provides a comparative analysis of the rites of passage (birth, marriage, and death) in Kahramanmaraş, one of Anatolia's deep-rooted cultural centers, and in Uzbekistan, the heart of the Silk Road. The study is grounded in Arnold van Gennep's theory of rites of passage and Bronislaw Malinowski's functionalist theoretical approaches. Both regions share a common historical foundation where pre-Islamic ancient Turkic-Shamanic beliefs are syncretically blended with Islamic practices. The study reveals striking similarities in both cultures regarding the legitimation of the individual's new status, the strengthening of social solidarity networks, and the management of crisis moments. However, significant differences were also identified in the physical and symbolic expressions of these rituals, shaped by geographical conditions, regional adaptations, and varying levels of modernization.
Keywords: Rites of Passage, Kahramanmaraş Folk Culture, Uzbek Culture, Cultural Memory, Comparative Folklore.